Saberes, cultura y mecenazgo en la correspondencia de las mujeres medievales - Muñoz Fernández, Ángela; Thieulin-Pardo, Hélène (Studies, 2021)
This book collects the interventions presented during the MISSIVA 2 conference which took place on May 6 and 7, 2019 at the Archivo Histórico Nacional and at the l'École des Hautes Études Hispaniques et Iberiques-EHEHI (Casa de Velázquez, Madrid). The aim of this meeting was to question the culture and knowledge of women in the light of their correspondence, their backing and patronage activities in the artistic, literary and religious fields or in the service of familial, dynastic and personal interests. The works presented unveil a wide variety of epistolary subjects and social profiles: queens of various European kingdoms, cultivated aristocrats, women of the bourgeoisie, women dedicated to international trade, abbesses, saints and nuns involved in the reform of the clergy.